Methane-related authigenic carbonates of eastern Mediterranean Sea mud volcanoes and their possible relation to gas hydrate destabilisation - Aloisi, G; Pierre, C; Rouchy, J M; Foucher, J P; Woodside, J (Earth and Planetary Science Letters, 2000)
Nautile submersible investigations of mud volcanoes and brine seep areas of the eastern Mediterranean Sea during the MEDINAUT cruise in November 1998 discovered extensive areas of authigenic carbonate crusts associated with methane emissions. Carbonate crusts form pavements, round slabs and circular mounds on the central, most active parts of mud volcanoes and in a fault-related valley where brines have accumulated to form a submarine brine lake. Authigenic carbonate nodules have been recovered from the same areas during the MEDINETH cruise in July 1999. Large 13C depletions of authigenic calcite, aragonite and dolomite indicate methane as a major carbon source for the carbonate. Crust pavements are formed when methane from a freshly emplaced, methane-charged mud flow is oxidised at the seafloor. In this environment, where bottom waters provide the sulphate and magnesium, aragonite is favoured versus calcite and accounts for the majority of the methane-related authigenic carbonates. Calcite, when present, contains significant amounts of Mg2+ (high-Mg calcite), and possibly other divalent ions in its crystal lattice. In areas of brine seep and accumulation, dolomitic nodules are present at shallow depth in the sediment. The 18O enrichment of the authigenic carbonates (up to 4‰ greater than calculated values for carbonates precipitating from modern eastern Mediterranean bottom waters) is interpreted as due to precipitation from 18O-rich fluids rather than as a temperature effect. The source of the 18O-rich fluids may be multiple and possibly includes the destabilisation of gas hydrates present at shallow subbottom depth, and the seepage of relic Messinian brines.